Réponses

2014-01-16T00:01:55+01:00
Bonsoir

Exercice 1

1) A = (3x - 1)² - (x + 2)²
         = (9x² - 6x + 1) - (x² + 4x + 4)
         = 9x² - 6x + 1 - x² - 4x - 4
         = 8x² - 10x - 3

2)  A = (3x - 1)² - (x + 2)²
          = [(3x - 1) + (x + 2)][(3x - 1) - (x + 2)]
          = (3x - 1 + x + 2)(3x - 1 - x - 2)
          = (4x + 1)(2x - 3)

3) A = 0
    (4x + 1)(2x - 3) = 0
    4x + 1 = 0   ou   2x - 3 = 0 
     4x = -1     ou    2x = 3
    x = -1/4    ou   x = 3/2

S = {-1/4 ; 3/2}


Exercice 2 

1) 5x - 6 = 7x - 9
5x - 7x = -9 + 6
-2x = -3
x = (-3)/(-2)
x = 3/2

S = {3/2}

2) x + 4 < 5x - 2
x - 5x < -2 - 4
-4x < -6
x > (-6)/(-4)
x > 3/2

S = ]3/2 ; +infini[